One-pot Electrochemical Synthesis of Ni Nanoparticles-Decorated Electroreduced Graphene Oxide for Improved NADH Sensing - Urhan, Bingul Kurt; Dogan, Hulya Ozturk; Ozer, Tuba Oznuluer; Demir, Umit (Wiley-V C H Verlag Gmbh, 2020)
Ni nanoparticles (NPs) decorated electrochemical reduced graphene oxide (NiNPs/ERGO) nanocomposites (NCs) on ITO electrode were successfully fabricated using one-pot simultaneously electrochemical co-reduction method at room temperature. The NiNPs/ERGO electrodes demonstrated very good electrocatalytic activity in the oxidation of NADH at a low oxidation potential (similar to+430 mV), a wide linear range (1-500 mu M), a calculated detection limit of 0.002 mu M. Compared to ERGO and NiNPs electrodes, the synthesized NiNPs/ERGO NCs have high electrocatalytic activity due to synergistic effect emerged between NiNPs and ERGO. The results indicated that the NiNPs/ERGO NCs can be easily prepared by one-pot electrochemical technique and NiNPs/ERGO could used to as potential biosensor for the NADH detection.
Keywords: Electrooxidation of NADH; Electrochemical reduction; reduced graphene oxide; NADH sensing; Ni nanoparticles